Impact of an acute coronary syndrome (ACS) specialist nurse service to reduce time to coronary angiography +/revascularisation. (2019) - Mathew, Tijo; Hayes, Michelle; Fenn, Hannah; Cutbert, Hadleigh; Carter-Jones, Clare; Rakhit, Roby; Lockie, Tim
No abstract available